2001
DOI: 10.1002/1615-9861(200108)1:8<975::aid-prot975>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Integrated system for high-throughput protein identification using a microfabricated device coupled to capillary electrophoresis / nanoelectrospray mass spectrometry

Abstract: An integrated microsystem providing rapid analyses of trace-level tryptic digests for proteomics application is presented. This modular microsystem includes an autosampler and a microfabricated device comprising a sample introduction port and an array of separation channels together with a low dead-volume facilitating the interface to nanoelectrospray mass spectrometry. Sequential injection and separation of peptide standards and tryptic digests was achieved with a throughput of up to 30 samples per hour with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…When coupled to an autosampler, this system provided sequential injection (1.5 l per injection) and separation of in-gel tryptic digests with a throughput of up to 25 samples/per h with less than 3% sample carryover. The concentration detection limit for peptide analysis was in the low micromolar range comparable with microfluidic devices of similar configuration (21,25). Although 1-2 l of sample was introduced to the large chip channel the overall sensitivity of this approach was limited by the actual injection volume on the chip device (typically Ͻ5 nl).…”
Section: Development Of a Sequential Injection Chip Device Withmentioning
confidence: 99%
See 3 more Smart Citations
“…When coupled to an autosampler, this system provided sequential injection (1.5 l per injection) and separation of in-gel tryptic digests with a throughput of up to 25 samples/per h with less than 3% sample carryover. The concentration detection limit for peptide analysis was in the low micromolar range comparable with microfluidic devices of similar configuration (21,25). Although 1-2 l of sample was introduced to the large chip channel the overall sensitivity of this approach was limited by the actual injection volume on the chip device (typically Ͻ5 nl).…”
Section: Development Of a Sequential Injection Chip Device Withmentioning
confidence: 99%
“…Obviously, significant advances in automation are still needed to provide the required throughput and ruggedness sought for the rapid and positive identification of proteins. To this end, efforts are also devoted to microfabricated chip designs that enable sample introduction from autosampler or microwell plates (24,25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Most reports on MCE-ESI-MS have focused on developing designs for facile interfacing of microfabricated devices with MS. [92][93][94]113,[126][127][128][129][130][131] Wen et al 126 demonstrated direct microchannel isoelectric focusing (IEF)-MS using a chip constructed on polycarbonate plates for the characterization of protein mixtures. Zhang et al 93 designed a microdevice from glass wafers, which integrated a guiding channel for insertion of the electrospray capillary.…”
Section: Ce-ms In Microfabricated Devicesmentioning
confidence: 99%